KARAKTER PELAJAR PANCASILA DALAM TEKS TUNGGAL BUKU BAHASA INDONESIA KEMENDIKBUDRISTEK - Ngatma'in Ngatma'in; Idhoofiyatul Fatin; Pheni Cahya Kartika; Taninda Mei Tantika (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This study aims to describe the character of Pancasila students presented in the single text of the Ministry of Education's Indonesian Language Book. The type of research is qualitative. The object of the research is a single text that contains the character of Pancasila students. Data collection techniques with documentation. Data analysis uses personal critical and creative thinking logic. The character of Pancasila students is presented in the discourse of short stories, argumentation, persuasion, and news. The character of faith and fear of God Almighty and noble character is seen in the text that describes the request for protection to God. The character of global diversity is seen in the text describing the stage of understanding the culture of society through social and economic approaches. The character of working together is seen in the text describing the stage of building a village group that produces local food sources. Creative characters are seen in the text describing the means of channeling technology-based creativity and innovation. Critical reasoning characters are seen in the text describing the process of understanding food source production data that is higher than the needs but the government continues to import rice. Independent character is seen in the text that explains food security and the nation's ability to produce airplanes.